2015
DOI: 10.1186/s40657-015-0033-y
|View full text |Cite
|
Sign up to set email alerts
|

Gender identification using acoustic analysis in birds without external sexual dimorphism

Abstract: Zoo and wildlife management faces a problem with bird sexing, as many bird taxa have indiscernible gender differences in size and coloration. Problematic groups are geese, cranes, rails, raptors, owls, parrots, doves, auks, shearwaters and some passerines. Commonly accepted invasive sexing techniques based on genetics, laparoscopy, morphometric and on cloacal inspection, are all needed in bird capturing and handling. Capturing and subsequent manipulations may be inapplicable for free-ranging birds, whereas dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 83 publications
1
35
0
Order By: Relevance
“…Physical characteristics, such as differences in color, size, alternative plumage (Rohwer, ), and presence or absence of features such as antlers in ungulates (Smith & McDonald, ), are used to differentiate ages, stages, or sex categories. Behavioral differences, including sexual segregation (Bowyer, ; Gregory, Lung, Gering, & Swanson, ) and alternative auditory song patterns (Volodin, Volodina, Klenova, & Matrosova, ), are another method used to classify individuals. Classifications are rarely perfect, creating a need to deal with the uncertainty that arises if only some individuals are classified.…”
Section: Introductionmentioning
confidence: 99%
“…Physical characteristics, such as differences in color, size, alternative plumage (Rohwer, ), and presence or absence of features such as antlers in ungulates (Smith & McDonald, ), are used to differentiate ages, stages, or sex categories. Behavioral differences, including sexual segregation (Bowyer, ; Gregory, Lung, Gering, & Swanson, ) and alternative auditory song patterns (Volodin, Volodina, Klenova, & Matrosova, ), are another method used to classify individuals. Classifications are rarely perfect, creating a need to deal with the uncertainty that arises if only some individuals are classified.…”
Section: Introductionmentioning
confidence: 99%
“…Discrimination of sex in poultry is done using different methods such as examining of feet, neck, feather colour and length as well as cloaca control, radiographic examination, footprint and hormonal or operational methods (Cerit and Avanus, 2007).Besides its importance for behavioural studies and wildlife management (Henry et al, 2015;Volodin et al, 2015), determination of sex is crucial for the profitability of agribusinesses. Zoometric measurement as a tool in sex discrimination has been examined in, for instance, mockingbirds (Fuchs and Montalti, 2016), owls (Tornberg et al, 2016), coots (Minias, 2015), Muscovy ducks (Oguntunji and Ayorinde, 2014) showing rather inconclusive results concerning predictability in terms of species and measurements traits.…”
Section: Introductionmentioning
confidence: 99%
“…However, others mechanisms of sex recognition by mother must be explored, for instance mechanisms based on vocal discrimination. Indeed, studies have reported sexual signature of calls in chicks from some avian species (Volodin, Volodina, Klenova, & Matrosova, 2015).…”
Section: Discussionmentioning
confidence: 99%